Accurate Numerical Solutions for Standard Skew Plate Benchmark Problems (Proceedings of Faculty of Civil Engineering, 2022)
Morley’s skew plate and Razzaque’s skew plate are two standard benchmark problems used for the performance evaluation of plate finite elements. The reference solutions for these problems are given for the thin plate case only, and various plate finite elements do not converge to these solutions exactly. Accurate numerical solutions for these skew plate problems are proposed in this paper, which are based on the finite element analysis on very dense meshes for thin to thick plate cases.
Keywords: Morley’s skew plate; Razzaque’s skew plate; plate finite elements; finite element analysis; accurate solutions; convergence; thin and thick plates